Do Elinor Ostroms principles of successful institutions illuminate the challenges to participation in groundwater governance in South Africa? What limits are there to using Ostrom's principles to analyse groundwater governance challenged in South Africa? - Rust, Jennifer (Department of Political Studies, 2017)
Elinor Ostrom's research has opened up a field of study into locally developed institutions for commons governance and has successfully disproved the notion that it is impossible for individuals to address collective problems cooperatively (Ostrom, 1993:110). South Africa has a semi-arid country with scarce water resources. Multiple diverse users such as farmers, private citizens, companies, and municipalities draw groundwater. Groundwater governance involves water allocation, regulation and management through socially acceptable institutions. This relationship between government and society is fundamentally a political one (Rogers, Hall, 2003). A primary concern of the new draft National Groundwater Strategy is governance and enabling the participatory processes involved (Department of Water and Sanitation, 2016). By drawing on Ostrom's principles of successful institutions to analyze groundwater governance challenges in South Africa it is evident that while her principles help to focus inquiry and largely reflect the literature on challenges to groundwater governance in South Africa. That said, Ostrom's principles may present an image of what aspects successful institutions tend to have, but these do not help us to develop a comprehensive understanding of the South African social and economic challenges to participatory institutional development. In South Africa the challenges of inequality and marginalization, and resulting social dynamics, as well as the issues of government capacity to be both a central actor and facilitative actor, and when each role is appropriate, are significant challenges to the sustainable governance of groundwater resources. The question of how to address these challenges must be addressed by government and all stakeholders if local participation is to be encouraged in South Africa.